Cognitive outcomes after extracranial-intracranial bypass surgery in elderly patients diagnosed with atherosclerotic cerebral steno-occlusive artery disease - Duan, Yu; Li, Jian; Zhang, Xin; Li, Shihong; Chai, Qiliang; Zhang, Yingying; Huang, Guohui; Xu, Ziwei; Li, Zhuyu; Mao, Renling; Dai, Dongwei (Frontiers in aging neuroscience, 2025)
The safety and clinical effectiveness of extracranial-intracranial (EC-IC) bypass surgery in elderly patients with atherosclerotic internal carotid artery and/or middle cerebral artery steno-occlusive (ACMSO) disease remain ambiguous. Here, we analyzed our experience of EC-IC bypass surgery to evaluate its clinical safety and effect on the cognitive function for elderly patients with ACMSO. This retrospective study enrolled patients >60 years of age diagnosed with ACMSO who underwent EC-IC bypass surgery at the authors' center between January 2018 and January 2021. Indications for bypass surgery included symptomatic ACMSO defined by cerebral angiography and evidence of relative hypoperfusion in the territories of steno-occlusive arteries based on computed tomography perfusion (CTP) neuroimaging. All patients underwent the Montreal Cognitive Assessment preoperatively and 2 years after bypass surgery. Clinical data, such as the National Institute of Health Stroke Scale and cognitive function scores, and CTP parameters were retrospectively analyzed. The study cohort ultimately included data from 65 patients (60-68 years of age; median age, 66 years) who underwent 82 bypass surgeries. The patency rate of bridge arteries was 100% on intraoperative fluoroscopy and 95.0% (76/80) according to cerebral angiography at the last follow-up. The perioperative stroke rate was 1.54 % and the mortality rate was 3.08% in the 2nd year of follow-up. Compared with preoperative data, the mismatch volume of CTP was reduced ( < 0.001), and the Montreal Cognitive Assessment score significantly increased ( < 0.001) 2 years after bypass surgery. Forty patients in the cognitive improvement group had a higher educational level ( = 0.020), shorter course of disease ( = 0.041), shorter mean transit time (MTT) ( < 0.001), and shorter time to peak value ( = 0.015) on CTP, as determined by single-factor analysis before bypass, compared with those in the inactive group. Based on multivariate logistic regression analysis, a shorter preoperative MTT was an independent clinical factor for cognitive improvement after bypass (odds ratio 0.452 [95% confidence interval 0.082-0.760]; = 0.003). EC-IC bypass surgery was safe and improved cognitive function in elderly patients diagnosed with ACMSO. Reversible cerebral perfusion function is one of the better prognoses, which needs to be confirmed in future study.